Dielectrophoretic assembly of dimpled colloids into open packing structures. Issue 34 (31st July 2017) - Jia, Zhuoqiang; Sacanna, Stefano; Lee, Stephanie S.
Abstract : Particle shape anisotropy enabled electric field-induced reversible solid-state phase transitions in two-dimensional colloidal crystals comprising dimpled spherical colloids. Abstract : Reversible solid-state phase transitions between open- and close-packed structures in two-dimensional colloidal crystals comprising 1.8 μm dimpled spherical colloids were observed using negative dielectrophoresis. These asymmetrically-shaped colloids adopted lattices with cmm plane group symmetry and a packing fraction, ϕ, of 0.68 at low electric field strengths. At high electric field strengths, the close-packed p 6 m symmetry was observed, with ϕ = 0.90. The transition between open and close-packed structures was found to be reversible, depending on the applied electric field strength and frequency. Finite Fourier transform analysis and COMSOL simulations revealed the existence of repulsive interactions between colloids perpendicular to the electric field lines due to a concentration of the electric field at the edges of the dimpled regions of the colloids. The repulsive interactions resulted in a stretching of the hexagonal lattice perpendicular to the electric field lines, the magnitude of which depended on the electric field strength. By screening the colloids from the electric field in local potential wells, the entropically favored close-packed hexagonal lattice with ϕ = 0.91 was recovered.